Development of IoT Real-Time Groundwater Monitoring System - Hawari, H.F. (IOP Publishing Ltd, 2021)
Internet of Things (IoT) Real-Time Groundwater Monitoring System is a system built to monitor groundwater extraction and consumption. Groundwater scarcity has become a major threat to the government especially water utility company. Water theft, inaccuracy meter reading & lock out access are some problems contributing to water scarcity. In this research, data obtained from the groundwater consumption using flow sensor will be sent to the server where all this data will be recorded for future analysing by respective authorities. The system has been tested thoroughly using of Long Range (LoRa) communication module together with Thingspeak cloud and mobile application. The results showed promising coverage with Line of Sight (LOS) is tested at 900m maximum while for Non-Line of Sight (NLOS) is at 600m. A very small standard deviation up to 4.93 was observed for received Signal Strength Indicator (RSSI) value for LOS and NLOS. Compared with the existing manual method, the proposed IoT system will water authority to monitor water consumption effectively through real time and better coverage. Â© 2021 Institute of Physics Publishing. All rights reserved.